EFL Teachers’ Strategies in Teaching Reading Skill in Lower Secondary School - Tri Wintolo Apoko; Widya Marcellinda (research, training and philanthropy institution Natural Aceh, 2023)
Reading is a receptive skill that students require, and it takes work to teach reading. Thus, teaching strategies for reading skills attracting students' interests are the keys to better reading comprehension. This study aimed to investigate EFL teachers’ strategies in teaching reading skills in lower secondary schools, how they implemented the strategies in teaching reading comprehension, and the student's responses. The method of this research was a qualitative design. The subjects of this research were six EFL teachers of SMPN 28 Tangerang, Banten. The instruments of this study were observation and interview. The study results showed four strategies the EFL teachers used in teaching reading skills: Scaffolding, Think-aloud, Question Answer Relationship (QAR), and Teacher as a Center. Thus, it is suggested that EFL teachers use various teaching strategies for reading skills to improve students' reading skills. The variety of EFL teachers' strategies would provide more pleasant and exciting learning atmospheres, encouraging the students to be interested in reading English texts.